Characterizing the contribution of plasticity and genetic differentiation to community‐level trait responses to environmental change. Issue 8 (23rd March 2018) - Lajoie, Geneviève; Vellend, Mark
Abstract: The match between functional trait variation in communities and environmental gradients is maintained by three processes: phenotypic plasticity and genetic differentiation (intraspecific processes), and species turnover (interspecific). Recently, evidence has emerged suggesting that intraspecific variation might have a potentially large role in driving functional community composition and response to environmental change. However, empirical evidence quantifying the respective importance of phenotypic plasticity and genetic differentiation relative to species turnover is still lacking. We performed a reciprocal transplant experiment using a common herbaceous plant species ( Oxalis montana ) among low‐, mid‐, and high‐elevation sites to first quantify the contributions of plasticity and genetic differentiation in driving intraspecific variation in three traits: height, specific leaf area, and leaf area. We next compared the contributions of these intraspecific drivers of community trait–environment matching to that of species turnover, which had been previously assessed along the same elevational gradient. Plasticity was the dominant driver of intraspecific trait variation across elevation in all traits, with only a small contribution of genetic differentiation among populations. Local adaptation was not detected to a major extent along the gradient. Fitness components were greatest in O. montana plants with trait values closest to the local community‐weighted means, thus supporting the common assumption that community‐weighted mean trait values represent selective optima. Our results suggest that community‐level trait responses to ongoing climate change should be mostly mediated by species turnover, even at the small spatial scale of our study, with an especially small contribution of evolutionary adaptation within species. Abstract : Studies partitioning the relative contributions of intraspecific variation (ITV) and species turnover (SPT) to community‐level trait variation have provided novel insights into community assembly and responses to environmental gradients over space and time. Still, empirical evidence quantifying the respective importance of the two drivers of ITV—phenotypic plasticity and genetic differentiation—relative to SPT is still lacking. We quantify the relative importance of these three drivers of community trait turnover to trait–environment matching among plant communities across a climatic gradient. Using a transplant experiment, we first show that phenotypic plasticity is consistently more important than local adaptation in driving intraspecific trait variation in our study species. Still, by comparing the size of these effects to that of species turnover among communities measured in parallel along the same gradient, we show that the contribution of plasticity remains marginal relative to species turnover, such that the latter should likely dominate community‐level responses to environmental change on the longer term. We validate the potential for comparison between trait–environment matching studies at the individual and community level by providing evidence that community‐weighted means indeed represent selective trait optima in our study species.